Answers

  • Brainly User
2015-07-26T10:23:11+05:30
S=ut+1/2 at²  It 2nd is equation of motion.
Here,
s=distance 
u=initial velocity
t=time 
a=acceleration
DERIVATION:











1 5 1
2015-07-26T17:07:08+05:30
S=ut+1/2at²
Derivation:
S=ut+1/2at²
⇒S=t(u+1/2at)
⇒S=t(u+1/2v)
⇒S=t(u+S/2t)
⇒S=ut+S/2
⇒S=(v-at)+vt/2
On solving more further and Substituting the values from the formulas v=S/t,v²=u²+2as
we will get:
S=2vt/2
⇒S=vt                                               as v=S/t so S=vt
⇒S=S
Hence proved
0